2016
DOI: 10.1007/978-3-319-40379-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Glass in Human–Robot Swarm Interaction

Abstract: Abstract. We study how a human operator can guide a swarm of robots when transporting a large object through an environment with obstacles. The operator controls a leader robot that influences the other robots of the swarm. Follower robots push the object only if they have no line of sight of the leader. The leader represents a way point that the object should reach. By changing its position over time, the operator effectively guides the transporting robots towards the final destination. The operator uses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Kapellman et al [37] suggested using Goolge Glass as physical support. These allow an operator to guide a swarm of robots for the transportation of an object.…”
Section: Shape Exploration Modementioning
confidence: 99%
“…Kapellman et al [37] suggested using Goolge Glass as physical support. These allow an operator to guide a swarm of robots for the transportation of an object.…”
Section: Shape Exploration Modementioning
confidence: 99%
“…Most modern mobile swarms are controlled by one or more operators [7]. They must follow the evolution of the robots and influence their performance if necessary, usually by assigning them a different goal to achieve [27]. However, this interaction depends on the communication mode between robots and humans [28]: speech, gesture, joystick or all of them.…”
Section: Related Workmentioning
confidence: 99%
“…Kapellman and al. [35] suggest using as physical support as Goolge Glass. These allow an operator to guide a swarm of robots for the transportation of an object.…”
Section: Shape Exploration Modementioning
confidence: 99%